The Impact of Institutional Frameworks on Private Sector Participation in Water Supply and Sanitation: The case of the management contract for water and wastewater services in the Amman Governorate, Jordan - Sylvia M. Steiner (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2008)
This research examines the impact of institutional frameworks on the performance of a private sector participation (PSP) arrangement in the water sector. The research takes place within the context of a development debate and practice, which identifies water as a key poverty issue in a substantial part of the developing countries, which advocates private sector participation as a remedy to inadequate water management and which acknowledges good governance as a crucial requirement for development. Nevertheless, few studies have scrutinized the impact of governance and institutions on the outcome of PSP arrangements in the water sector. Most research on the performance of PSP arrangements has examined exogenous and endogenous determinants, such as the price mechanism and the property rights allocation, but these factors proved unsatisfactory as explaining variables in the context of natural resource management. To contribute to filling a gap in research this study aims at evaluating the impact of institutional frameworks on the outcome of private sector participation in water supply and sanitation through a case study of the Management Contract for Water and Wastewater Service in the Amman Governorate, Jordan. The research takes into account the specific institutional framework for the mentioned arrangement in Amman, which is comprised of the national judicial and political institutions, the specific regulatory institutions as well as relevant international institutions. The specific objective of this study is to show how the institutional framework of a transaction affects regulatory processes by abating and amplifying the potential for opportunistic behavior of the contracting parties, and thereby affecting the performance of a privately operated water utility. The examination of the institutional framework of the Amman Management Contract revealed that mainly judicial and international institutions and specific contract rules were constraining the discretion of the contracting parties. Political checks and balances were insufficiently established and the regulatory institutions of the water sector were set up in an improper way. The field study discovered that the resulting discretionary power of certain actors was used opportunistically, which had a detrimental effect on the outcome of the PSP arrangement. Nevertheless the overall performance of the arrangement was good from which the general insight was drawn that regulatory credibility may be developed even in unpropitious environments.
Keywords: 320; Jordan; Water supply; Sanitation; Private sector; Wasserpolitik; Wasserversorgung; Wasserwirtschaft; Kanalisation; Abwasserwirtschaft; Governance-Ansatz; Privatisierung; Institutionelle Infrastruktur; Wirkungsanalyse; Amman; Jordanien